2019
DOI: 10.1021/acs.jpcb.9b02277
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution 17O NMR Spectroscopy of Structural Water

Abstract: The importance of studying site-specific interactions of structurally similar water molecules in complex systems is well known. We demonstrate the ability to resolve four distinct bound water environments within the crystal structure of lanthanum magnesium nitrate hydrate via 17O solid state nuclear magnetic resonance (NMR) spectroscopy. The approach utilizes high-resolution multi-dimensional 17O NMR experiments at high magnetic fields (18.8 – 35.2 T) where each individual water environment was resolved. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 77 publications
4
32
0
Order By: Relevance
“…4, 5 17 O quadrupole central transition has also been used to study chemical and biological macromolecules in solution as reported in the literature. 4,[6][7][8][9] In this study, polymer nanodiscs are used as membrane mimetics to investigate the interaction of water with lipid bilayer using natural-abundance 17 O NMR spectroscopy. Polymer nanodiscs consists of a planar lipid bilayer encased by the polymer belt (Fig.…”
mentioning
confidence: 99%
“…4, 5 17 O quadrupole central transition has also been used to study chemical and biological macromolecules in solution as reported in the literature. 4,[6][7][8][9] In this study, polymer nanodiscs are used as membrane mimetics to investigate the interaction of water with lipid bilayer using natural-abundance 17 O NMR spectroscopy. Polymer nanodiscs consists of a planar lipid bilayer encased by the polymer belt (Fig.…”
mentioning
confidence: 99%
“…2(d) corresponds to the water molecules in the DNP juice and was simulated assuming quadrupolar parameters for ice reported in the literature. [36,37] The shift parameters were calculated ex-novo in this study for a cluster of 6 water molecules (See Supporting Information). The simulated linewidth, which is mostly due to second-order quadrupole interactions, reproduces very well the linewidth observed experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…As the secondorder quadrupolar broadening is inversely proportional to the Larmor frequency, the width of the lineshape decreases with increasing magnetic field strength, meaning that measurements at higher magnetic fields are preferable to achieve higher resolution. [36][37][38][39] Here, the first set of 1D 17 O MAS NMR spectra of BM 5min À SiO 2 and BM 15min À SiO 2 was thus recorded at 18.8 T (Figure 2b). At this field, while siloxane and silanol resonances still overlap, [18,33] a distinct resonance centered at À 12.1 ppm is clearly observed for the BM 5min À SiO 2 phase, the 17 O chemical shift of which is consistent with water.…”
Section: Enrichment Level and Model Of The Surface Labelingmentioning
confidence: 99%